Anesthesia in a patient with multiple symmetric lipomatosis: A case report (Research, Society and Development, 2024)
Multiple symmetric lipomatosis (Madelung's disease) is a pathology characterized by the accumulation of fat in specific anatomical areas, mainly around the cervical region and limbs. The objective of this study is to present a case report regarding an anesthetic procedure in a patient with the condition undergoing elective laparoscopic cholecystectomy. The patient, an adult man with obesity, a history of alcoholism, liver cirrhosis, and obstructive sleep apnea syndrome, underwent pre-anesthetic evaluation, during which predictors of difficult intubation and ventilation were identified, along with the report of Madelung's disease. Consequently, as part of the anesthetic planning, the patient was subjected to awake laryngoscopy using topical airway anesthesia and a videolaryngoscope approach. The patient was then placed under general anesthesia, and the procedure proceeded without complications. Patients with this syndrome present challenges concerning airway management. For that reason, a detailed anesthetic plan and access to airway devices for difficult airway management, such as a bougie, fiber optic scope, and equipment for surgical airway access, are necessary. Additionally, patients with lipomatosis may exhibit unique pharmacokinetic properties regarding anesthetic drugs due to their altered lipid composition. Therefore, it is evident that special attention is required for patients with this syndrome due to potential complications in anesthetic management, both in elective and emergency contexts.